Outcomes and complications of orthognathic surgery in older patients - Liesbeth Govaers; Renée Beckers; Constantinus Politis (Elsevier, 2024)
Purpose: Several studies have described the outcomes and complications following orthognathic surgery. However, the average patient age in these studies is 20-40 years. It is unclear whether results from these age groups can be extrapolated to older patients. Methods: This retrospective observational study included 54 patients over 50 years of age, who underwent orthognathic surgery. From these patients' medical records, we retrieved data regarding patient characteristics, surgery characteristics, outcomes, and complications. Results: The patients' mean age was 56 years (range, 50-69 years), and mean ASA score was 2. A bad split occurred in one patient, and immediate postoperative complications occurred in two patients. There were no long-term sequelae. Neurosensory disturbances (NSD) occurred in 30 patients. Preoperative temporomandibular dysfunction (TMD) was present in 9 patients-among whom, five were cured after surgery. Four patients postoperatively developed de novo TMD. Hardware removal was performed in 22 patients. The mean length of stay was two days for monomaxillary procedures, and three days for bimaxillary procedures. Conclusions: This study demonstrated apparent differences between patients over 50 years of age and the general orthognathic population. In particular, neurosensory disturbances and hardware removal were more prevalent in our study population.